The Road to Recovery #4: Evaluating Virtual Techniques to Reach Clientele and Promote Equity - Colby Jordan Silvert; Cody Gusto; John Diaz; Glenn Israel (EDIS)
This fourth publication in the Road to Recovery series explores the challenges Extension professionals may encounter in reaching clientele virtually during a pandemic. This new 4-page publication of the UF/IFAS Department of Agricultural Education and Communication discusses the concept of digital equity and provides recommendations to evaluate efforts to access and connect with key audiences. Written by Colby Silvert, Cody Gusto, John Diaz, and Glenn Israel. https://edis.ifas.ufl.edu/wc387